Fiber coupled 1 kW repetitively acousto-optic Q-switched cw-pumped Nd:YAG rod laser. (August 2019) - Wang, Yibo; Zhang, Zhiyan; Liang, Hao; Qu, Shengchun; Gao, Jiancun; Lin, Xuechun
Highlights: We demonstrate firstly 1 kW level fiber coupled cw-pumped Q-switched laser in detail. Low-order aberrations add difficulties to high efficiency of optical fiber coupling. It generates 1022 W at 1.06 μm with 102 ns at 20 kHz from a 300 μm 0.22 NA fiber. The laser will be competitive and effective in laser ablation. Abstract: With MOPA configurations, a fiber coupled 1 kW repetitively acousto-optic Q-switched cw-pumped Nd:YAG rod laser is studied in detail. Low-order aberrations introduced by MOPA systems add difficulties to high efficiency of optical fiber coupling. With 300 μm 0.22 NA fiber coupled, an average power of 1022 W along with 102 ns pulse width at 20 kHz is obtained with 11.6% electro-to-optical efficiency and 93% fiber coupling efficiency, and the corresponding peak power is about 500 kW. The power stability is better than 0.93% at the maximum output power in an hour.